Green Product: Our Response to Environmental sustainability - Joseph, Biju (IJRDO-Journal of Applied Science, 2017)
In achieving sustainable development Green products and the consumers’ preferences for it areimportant. Present world realises the importance of green environment. So more and more initiatives arecoming up in different parts of the world. These initiatives in production and consumption may lead to abetter environment around us. The purpose of this study is to assess the awareness and attitude ofconsumers regarding green products and to identify the factors which act as an obstacle to green lifestyle. To conduct the study MALAPPURAM district of Kerala State is selected. Primary and secondarydata was collected from various resources. This data was analysed with suitable statistical. The analysisreveals that the people have special concern towards the environmental protection and that is whymajority of the people opt for organic products. Such an attitude by the people helps the movement ofsustainable development.